2006
DOI: 10.1083/jcb.200512025
|View full text |Cite
|
Sign up to set email alerts
|

A specialized processing body that is temporally and asymmetrically regulated during the cell cycle in Saccharomyces cerevisiae

Abstract: RNase mitochondrial RNA processing (MRP) is an essential ribonucleoprotein endoribonuclease that functions in the degradation of specific mRNAs involved in cell cycle regulation. We have investigated where this processing event occurs and how it is regulated. As expected, results demonstrate that RNase MRP is predominantly localized in the nucleolus, where it processes ribosomal RNAs. However, after the initiation of mitosis, RNase MRP localizes throughout the entire nucleus and in a single discrete cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…First, RNase MRP was shown to cleave the 59 UTR of the CLB2 (Cyclin B2) mRNA (Gill et al 2004). (RNase MRP, generally a nucleolar enzyme, was shown to transiently accumulate in a discrete cytoplasmic spot where it co-localizes with the CLB2 mRNA [Gill et al 2006]). In vitro cleavage assays performed on the 59 UTR of CLB2 mRNA confirm previously reported (Gill et al 2004) RNase MRP cleavage at sites that are consistent with the identified consensus (Supplemental Fig.…”
Section: Cleavage Of Known Rnase Mrp Substratesmentioning
confidence: 99%
“…First, RNase MRP was shown to cleave the 59 UTR of the CLB2 (Cyclin B2) mRNA (Gill et al 2004). (RNase MRP, generally a nucleolar enzyme, was shown to transiently accumulate in a discrete cytoplasmic spot where it co-localizes with the CLB2 mRNA [Gill et al 2006]). In vitro cleavage assays performed on the 59 UTR of CLB2 mRNA confirm previously reported (Gill et al 2004) RNase MRP cleavage at sites that are consistent with the identified consensus (Supplemental Fig.…”
Section: Cleavage Of Known Rnase Mrp Substratesmentioning
confidence: 99%
“…RNase MRP is also implicated in messenger RNA (mRNA) degradation and cell cycle progression at the end of mitosis. It processes the 5′-UTR of the cyclin B2 (CLB2) mRNA and regulates the completion of mitosis [8,9].…”
Section: The Function Of Rnase Mrpmentioning
confidence: 99%
“…Yeast RNase MRP is also involved in the regulation of the cell cycle by cleaving the 59 UTR of cyclin B2 mRNA (Cai et al 1999(Cai et al , 2002Gill et al 2006). Defects in RNase MRP function result in a variety of recessive pleiotropic diseases typically characterized by dwarfism (Ridanpaa et al 2001;Thiel et al 2005;Martin and Li 2007;Glazov et al 2011); the mechanisms responsible for the development of these diseases are not known.…”
Section: Introductionmentioning
confidence: 99%
“…RNase MRP is essential for the viability of eukaryotes (Schmitt and Clayton 1992;Schneider et al 2010). Though it was originally identified as a mitochondrial enzyme, the vast majority of RNase MRP is found in the nucleolus and, transiently, in the cytoplasm (Chang and Clayton 1987a;Karwan et al 1991;Gill et al 2006, and references therein). Mitochondrial RNase MRP has a distinct protein composition which is yet to be fully characterized (Lu et al 2010) and will not be discussed in this study.…”
Section: Introductionmentioning
confidence: 99%